2001
DOI: 10.1002/1099-0690(200107)2001:14<2665::aid-ejoc2665>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-1-azacyclohexa-2,3-diene(N−B)borane − Generation and Interception of an Unsymmetrical Isodihydropyridine

Abstract: Keywords: Allenes / Amines / Boranes / Cycloadditions / Eliminations / Strained molecules 3-Bromo-1-methyl-1,2,5,6-tetrahydropyridine(N−B)borane (7) was prepared from 3-bromopyridine by conversion to 3-bromo-1-methylpyridinium iodide, hydrogenation of the latter with sodium tetrahydroborate and treatment of the resulting 3-bromo-1-methyl-1,2,5,6-tetrahydropyridine (6) with borane−dimethyl sulfide. Whereas no trapping product of the possible intermediate 1-methyl-1-azacyclohexa-2,3-diene (4) could be observed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…164 An unsymmetrical isodihydropyridine (an 1azacyclohexa-2,3-diene prepared by base-induced dehydrohalogenation of a 3-bromo-1,2,5,6-tetrahydropyridine) was efficiently trapped by [4 ϩ 2] and [2 ϩ 2] cycloadditions with furan and styrene, respectively. 165 The photocycloaddition of cyanoethylenes onto 1,4-dihydropyridines has been reported. Photoirradiation of N-alkoxycarbonyl-1,2-dihydropyridines 105 promoted the concerted electrocyclization to yield the 2-azabicyclo[2.2.0]hexene system 106, which was, afterwards, successfully transformed into a variety of rearranged and nonrearranged skeletal types 107-109 (Scheme 29).…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
“…164 An unsymmetrical isodihydropyridine (an 1azacyclohexa-2,3-diene prepared by base-induced dehydrohalogenation of a 3-bromo-1,2,5,6-tetrahydropyridine) was efficiently trapped by [4 ϩ 2] and [2 ϩ 2] cycloadditions with furan and styrene, respectively. 165 The photocycloaddition of cyanoethylenes onto 1,4-dihydropyridines has been reported. Photoirradiation of N-alkoxycarbonyl-1,2-dihydropyridines 105 promoted the concerted electrocyclization to yield the 2-azabicyclo[2.2.0]hexene system 106, which was, afterwards, successfully transformed into a variety of rearranged and nonrearranged skeletal types 107-109 (Scheme 29).…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
“…A diverse range of stereochemically‐rich products can be accessed via highly endo selective Diels–Alder cycloadditions to strained cyclic allenes, as shown by cycloadducts 1 – 4 (Figure 1 a). [2b–e] Our groups [2c,d,f–i] and others [2j,k] have generated strained cyclic allenes from silyl triflates, 5 , and have found that in situ generated heterocyclic allenes, such as unsubstituted allenes 7 and 8 , participate in highly endo selective Diels–Alder reactions to provide adducts 13 – 22 (Figure 1 b). [2c,d] …”
Section: Introductionmentioning
confidence: 99%
“…More recently, efforts were focused on the isomeric 1-aza-2,3-cyclohexadiene. Although this was found to be unstable, N -borylation permitted access to azacyclic allene 8 26 . Additional discoveries in this field include the synthesis of a cephalosporinderived cyclic allene formation by Elliott and co-workers 2729 and several studies pertaining to heterocyclic isoarenes 7,3036 .…”
mentioning
confidence: 99%